PENGARUH DOSIS PUPUK NITROGEN DAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN DAN HASIL JAGUNG HIBRIDA (Zea Mays L) VARIETAS PIONEER 21 - Kusmanto Kusmanto; AF Aziez AF Aziez; Tyas Soemarah KD Tyas Soemarah KD (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2010)
This research aim to know nitrogen fertilizer dose influence and goat manure to growth and result of corn crop ( Zea Mays L) variety Pioneer. Writing of this skripsi based on research from date of 23 Februari 2008 until date of 7 June 2008 in countryside Kedokan Sayang, subdistrict Tarub, district Tegal with place height Â± 25 m dpl. Grey alluvial soil type of stripper. Research method applied is factorial method with Rancangan Acak Kelompok Lengkap (RAKL), consisted of two medium treatment factors of treatment firstly composes kinds of second nitrogen fertilizer dose and treatment is goat manure. As for its(the factor is as follows : First factor of nitrogen fertilizer dose, consisted of 4 level : N0 : Fertilizer dose Urea ( Nitrogen) = 0 kg/ha, N1 : Urea fertilizer dose ( Nitrogen) : 200 kg/ha, N2 : Urea fertilizer dose ( Nitrogen) : 300 kg/ha. N3 : Urea fertilizer dose ( Nitrogen) : 400 kg/ha. Second factor of goat manure dose consisted of 3 level K1: goat manure : 10 ton/ha, K2 : goat manure : 15 ton/ha, K3 : goat manure : 20 ton/ha thereby is got 12 combinations to treat. Result of this research nitrogen fertilizer influential very differing in reality to plant height, wet weight overall of crop, drought weight overall of crop, number of seeds per cob, weight pipilan drought per crop, weight pipilan drought per check and heavy 100 seeds. Only line amounts per cob having an effect on differs in reality. Weight pipilan per highest check reached at combination of fertilizer dose N2 : 300 kg/ha with goat manure dose 15 ton/ha that is ( 9329,2 ton/ha). result of this research as according to Hipotesis that is with best result of N2K2.